Etude de L’évolution Diachronique de La Gleba Celeste (mato Grosso) à Partir D’images Landsat (Revista Espaço e Geografia, 2022)
The implementation and the development of the Gleba Celeste, in the Central-North of Mato Grosso, constitute a symbol of the recent occupation of the Amazônia south border. The growth of the Sinop city and neighbors county like Vera, Cláudiaand Santa Carmem, testifies the expansion vitality of the pioneering front in this region.The Landsat satellite images allow to visualize and to schematize the expansion phasesthat lead to a new areas the growth of increasing deforestation practices characterizingthe urban center stage.